Optimasi Dosis Pemupukan Nitrogen pada Budidaya Bayam Cabut (Amaranthus viridis) dalam Polibag - Oktaviana Rosario Sere Gili; Yovita Yasintha Bolly; Marianus Mayolis (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Nitrogen is an essential macronutrient that plays a crucial role in supporting plant growth and development. This nutrient is generally absorbed by plants in the form of ammonium (NH₄⁺) and nitrate (NO₃⁻) ions. The effectiveness of nitrogen fertilization is strongly influenced by the type of fertilizer and the applied dosage. This study aimed to evaluate the effects of different nitrogen fertilizer sources and application rates on the growth and yield of spinach (Amaranthus viridis) cultivated in polybags. The experiment was conducted at the Experimental Farm of Nusa Nipa University from February to March 2026 using a factorial Randomized Complete Block Design (RCBD) with three replications. The first factor consisted of two nitrogen sources, namely urea and calcium ammonium nitrate, while the second factor consisted of five nitrogen application rates: 0X, ¼X, ½X, ¾X, and X (recommended dose). The results showed that different nitrogen sources did not significantly affect plant height, leaf number, fresh weight, dry weight, or plant water content. In contrast, increasing nitrogen rates significantly affected plant height at 2 weeks after planting (WAP) and plant dry weight. The interaction between nitrogen source and application rate exhibited a linear response for plant height at 3 WAP and fresh weight.